Math Puzzles and Free Play: Which is More Effective for Children's Spatial Development? - Al Ayyubi, Ibnu Imam; Nurhikmah; Noerzanah, Firda; Prayetno, Eko; Asri, Muhammad Rizal (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
This study aims to compare the effectiveness of learning using math puzzles (game-based learning) with free play (play-based learning) in developing spatial abilities of early childhood. This study uses a mixed methods approach with an explanatory sequential design. The sample of the study consisted of 30 students, 15 students at TK Inpres Mannurukki (experimental class) and 15 students at TK IT At-Tibyan (control class), with a purposive sampling technique. The instruments used were tests and interviews. Quantitative data were analyzed using descriptive and inferential statistics through SPSS 26, including normality tests, variance homogeneity tests, Mann-Whitney tests, Independent Samples t-tests, and N-Gain tests. Qualitative analysis was carried out using thematic analysis. The results showed that in the posttest, the average score of the experimental class (math puzzle) was 76.13, while the control class (free play) reached 84.20. Statistical tests showed a significant difference (p = 0.014), with the control class showing better results. However, the N-Gain test in the experimental class showed moderate effectiveness with an average N-Gain value of 0.599. Interviews with students showed that mathematical puzzle-based learning increased motivation and interest in learning, although some students had difficulty with the level of puzzle difficulty being too high. In contrast, students in the control class felt freer, but needed more guidance to link the game to mathematical concepts. This study concluded that although mathematical puzzles are interesting, free play-based learning is more effective in supporting the overall development of mathematical concepts in early childhood.